Spectrum of Primary Gastric Lymphoma in India: A Series of 30 Patients - Mathur, Akash; Ghoshal, Uday C.; Kumar, Sushil; Kumari, Neeraj; Krishnani, Narendra (Turkish Journal of Gastroenterology, 2022)
Background: Primary gastric lymphoma is uncommonly reported in India. We retrospectively analyzed their data in a northern Indian teaching hospital.Methods: During a 12-year period (2000-2012), endoscopic and surgical biopsies were assessed for gastric neoplasm. Gastric biopsies from normal-looking areas, rapid urease test, and Helicobacter pylori serology were done, with 2 of 3 tests positive being considered diagnostic. We aimed to study (i) the frequency of primary gastric lymphoma among gastric neoplasm patients, (ii) its clinical profile, (iii) the diagnostic procedures needed, and (iv) the frequency of H. pylori infection among them.Results: Thirty out of 324 (9.2%) patients (age 56 years, range 25-72, 73.3% male) with gastric neoplasm had primary gastric lymphoma. Presentations included dyspepsia (n = 9, 30%), gastric outlet obstruction (n = 7, 23.3%), upper gastrointestinal bleeding (n = 5, 16.7%), dysphagia (n = 4, 13.3%), malignant ascites (n = 3, 10%), and others (n = 2, 6.7%). H. pylori infection was confirmed in 7 (23.3%), 12 (40%), and 21/29 (72.4%) patients by rapid urease test and histopathology and positive anti-H. pylori IgG serology, respectively. By 2 tests, H. pylori was detected in 12 (40%) patients. Though in 60% primary gastric lymphoma was diagnosed on endoscopic biopsy, in 40%, surgical resection was required. The endoscopic and surgical diagnosis groups were comparable in age (53.4 years vs. 52.7 years), sex (male 77.8% vs. 66.7%), H. pylori infection (38.9% vs. 16.7%), presentation with dyspepsia (38.9% vs. 16.7%), organic symptoms (61.1% vs. 83.3%), and the need for repeated endoscopic biopsies before diagnosis (12.% vs. 33.3%).Conclusion: Primary gastric lymphoma is not uncommon (9.2%) in India, often missed on endoscopic biopsy and is associated with H. pylori infection (40%)Cite this article as: Mathur A, Ghoshal UC, Kumar S, Kumari N, Krishnani N. Spectrum of primary gastric lymphoma in India: A series of 30 patients. Turk J Gastroenterol. 2023;34(2):135-139.